2014
DOI: 10.1111/eje.12092
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in self‐assessed clinical competence– a survey of young dentists in Finland

Abstract: The gender differences in young dentists' confidence-which favoured male dentists-require further inquiries. More attention should be paid in dental education to constructively support students with differences in learning clinical skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 16 publications
6
32
0
Order By: Relevance
“…And do we risk losing competent GDPs to specialism with primary care suffering at the expense of secondary care? This is significantly less when compared with the situation in Sweden where 77% of 166 graduates expressed a desire for specialist training in a follow‐up survey of graduates from 1995 to 1999 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…And do we risk losing competent GDPs to specialism with primary care suffering at the expense of secondary care? This is significantly less when compared with the situation in Sweden where 77% of 166 graduates expressed a desire for specialist training in a follow‐up survey of graduates from 1995 to 1999 .…”
Section: Discussionmentioning
confidence: 77%
“…We found in the initial survey men were more positive about their surgical skills than women. A recent study of Swedish dentists also found this apparent gender difference . However, this was not the case in the follow‐up survey and so the authors postulate whether this could represent another form of reporting bias as half of the women responding had spent time in oral surgery or OMFS?…”
Section: Discussionmentioning
confidence: 95%
“…In addition, most of our infection preventionists are women, and some data show that women tend to undervalue their knowledge and competence. [7][8][9][10] Given the low numbers of male infection preventionists in our program, we are unable to perform comparisons by sex. Acknowledging that there is no gold standard for defining competence beyond the CIC designation, we did not have a good reference for assigning which questions within our OA would indicate the expert career stage.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of undergraduate endodontic education on the students' perception of preparedness for performing endodontic treatment was measured differently in several previous studies (3)(4)(5)(6)(7)(8). In the absence of a gold standard, a new questionnaire was composed for the present study to survey students' perception of their competence and their confidence.…”
Section: Hardly True Moderately Truementioning
confidence: 99%
“…There are conflicting reports about how well, in their own perception, dental graduates or students who are about to graduate had been prepared for their work as general dental practitioner by their undergraduate endodontic education (3,4). Many of them felt unprepared and not very confident (5-7) about performing complex endodontic treatments.…”
Section: Introductionmentioning
confidence: 99%